Prokaryotic Population Dynamics and Viral Predation in a Marine Succession Experiment Using Metagenomics - Haro-Moreno, Jose M.; Rodriguez-Valera, Francisco; López-Pérez, Mario (Frontiers in Microbiology, 2019)
We performed an incubation experiment of seawater confined in plastic bottles with samples collected at three depths (15, 60 and 90 m) after retrieval from a single offshore location in the Mediterranean Sea, from a late summer stratified water column. Two samples representative of each depth were collected and stored in opaque bottles after two periods of seven hours. We took advantage of the “bottle effect” to investigate changes in the natural microbial communities (abundant and rare). We recovered 94 metagenome-assembled genomes and 1,089 metagenomic viral contigs and examined their abundance using metagenomic recruitment. We detected a significant fast growth of copiotrophic bacteria such as Alteromonas or Erythrobacter throughout the entire water column with different dynamics that we assign to “clonal”, “polyclonal” or “multispecies” depending on the recruitment pattern. Results also showed a marked ecotype succession in the phototropic picocyanobacteria that were able to grow at all the depths in the absence of light, highlighting the importance of their mixotrophic potential. In addition, “wall-chain-reaction” hypothesis based on the study of phage-host dynamics showed the higher impact of viral predation on archaea in deeper waters, evidencing their prominent role during incubations. Our results provide a step forward in understanding the mechanisms underlying dynamic patterns and ecology of the marine microbiome and the importance of processing the samples immediately after collection to avoid changes in the community structure.